A Polymer Electrolyte Containing Solvate Ionic Liquid with Increased Mechanical Strength Formed by Self-assembly of ABA-type Ionomer Triblock Copolymer. (1st May 2017) - Kawazoe, Takayuki; Hashimoto, Kei; Kitazawa, Yuzo; Kokubo, Hisashi; Watanabe, Masayoshi
Highlights: Polymer electrolytes consisting of ionomer triblock copolymer and an ionic liquid are prepared. The tensile properties are greater than those of a nonionic block copolymer electrolyte. Thermal stability, high ionic conductivity, and electrochemical stability is attained. Abstract: Polymer electrolytes containing solvate ionic liquids (SILs) with increased toughness for use in lithium secondary batteries were designed by utilizing the self-assembly of ABA-type ionomer triblock copolymer, where the A-blocks are ionomers having strong intermolecular coulombic interactions. The ABA-type triblock copolymer, poly(lithium acrylate- r -acrylic acid)- b -poly(methyl methacrylate)- b -poly(lithium acrylate- r -acrylic acid) (P(LiA- r -AA)- b -PMMA- b -P(LiA- r -AA), denoted LML), was synthesized and used as the polymer electrolytes host matrix. The fundamental properties, such as rheological, mechanical, and electrochemical properties, were explored for a binary system (ion gel) comprising LML and a hydrophobic ionic liquid. Due to the strong Li + -carboxylate interactions, the tensile fracture energy of the ion gel was greatly enhanced compared to those of conventional block copolymer electrolytes using nonionic polymers, indicating that the use of the ionomer in the A-block contributed to an enhancement in the tensile strength. Furthermore, the polymer electrolytes prepared with SILs showed good Li + -conductivity and thermal stability. Electrochemical potential window of the polymer electrolytes, revealed by voltammetry, demonstrated their oxidation stability up to 4.5 V vs. Li/Li + and reversible lithium deposition and dissolution.